An evaluation of the implications of the revised HIV deployment policy on the healthcare service of the South African National Defence Force - Nxumalo, Busiswe Letty (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.